Neuroprotective effects of taurine and 3-hydroxypyridine derivatives in the intracerebral hemorrhage model in rats - Natalia I. Nesterova; Olesya V. Shcheblykina; Pavel D. Kolesnichenko; Arkady V. Nesterov; Dmitry V. Shcheblykin; Dmitry Yakovlev (Belgorod National Research University, 2019)
Introduction: At present, the problem of pharmacological correction of free radical processess emerges full-blown. The aim of the study is an experimental study of the neuroprotective effect of taurine and 3-hydroxypyridine derivatives. Materials and methods: The study was performed in Wistar rats. The neuroprotective effect of the substances was studied in the intracerebral hemorrhage model. Results and discussion: The administration of the studied substances had a positive effect on the survival of the animals within the first day (50% of rats died in the control group, 30% - in the Mexidol- and Ethoxidol-treated groups, and 20% - in LKhT 3-17-treated group). Within the first day after the surgery, all rats with stroke had severe neurological disorders. However, by the 3rd day, the Ethoxidol- and LKhT 3-17-treated rats had a lower neurological deficit. By Day 14, all groups of animals treated with the test substances had a lower severity of post-stroke disorders than those in the control group, which was evident as a 1.5-time lower McGraw Stroke Index score. LKhT 3-17 substance showed the most pronounced neuroprotective effect. Conclusions: The studied derivatives of taurine and 3-hydroxypyridine have a neuroprotective effect, which is manifested in the lower severity of neurological disorders,a more rapid reduction in the signs of neurodegeneration and accelerated hemorrhage processes.